2022
DOI: 10.1177/17585732221076066
|View full text |Cite
|
Sign up to set email alerts
|

What is the Optimal Construct to Reduce Failure in Arthroscopic Four Anchor Rotator Cuff Repair?

Abstract: Background Re-tear following rotator cuff repair (RCR) is a concerning complication that can lead to poor patient outcomes and necessitate the need for revision surgery. The purpose of our study was to look at the combined construct of knotted vs. knotless medial row and suture vs. suture tape, focusing primarily on re-tear rates following surgery. Methods A retrospective observational study of 343 consecutive patients undergoing arthroscopic double row, 4-anchor rotator cuff repair from February 2014 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A study found a lower rate of re-rupture in individuals who had double row repair, albeit it did not make a functional distinction between the two procedures. The efficiency of corrected rotator cuff tears is highly correlated with the degree of activity after surgery (10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…A study found a lower rate of re-rupture in individuals who had double row repair, albeit it did not make a functional distinction between the two procedures. The efficiency of corrected rotator cuff tears is highly correlated with the degree of activity after surgery (10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…Various surgical techniques, from the single-row to the transosseous equivalent technique, 16,20 have been employed to decrease the retear rate, but achieving enthetic regeneration can be challenging, and disorganized scar tissue often forms at the bone-tendon interface. To enhance healing and induce regeneration of functional tissues, biologic strategies such as platelet-rich plasma (PRP), 2,4,19 mesenchymal stem cells, growth factors, and cytokines have been investigated.…”
mentioning
confidence: 99%